Produksi Set Meja dan Kursi Teras Rumah Tinggal pada Nave Wood Furniture: Furniture - Mamo Antonius Wilibrodus; Mudra I Wayan; Suparta I Made (Pusat Penerbitan LPPM ISI Bali, 2026)
This paper discusses the process of designing and manufacturing a set of tables and chairs for a residential terrace, considering functional, aesthetic, and user comfort aspects. This activity was carried out as part of the Independent Learning Campus (MBKM) program of the Indonesian Arts Institute, Bali, which was implemented at the Nave Wood furniture business partner in 2025. Data collection was carried out using observation, interviews, documentation, and qualitative descriptive data analysis. The design planning, material and tool selection, and production process were carried out directly by the author at the partner's location. The main material used is solid wood, which is resistant to outdoor weather. The result of this MBKM implementation is a table and chair product that not only meets the need for seating on the terrace but also beautifies the appearance of the residence. This activity also provided the author with direct experience as a student in enriching insight into the field of furniture, mastery of woodworking techniques, tool use, and finishing processes. Through this activity, students were also able to develop creative and innovative thinking according to market needs. The final result of this MBKM activity is a table and two chairs made of Dutch teak wood with strong construction and a simple design, according to the user's needs and the character of the terrace space. Additional products created to complement the table include a mineral water container, a cake stand, and a flower vase made from leftover wood.